2007
DOI: 10.1097/01.aog.0000267201.70965.ec
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coital Activity on Onset of Labor in Women Scheduled for Labor Induction

Abstract: isrctn.org, http://isrctn.org, ISRCTN17998696

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
3
11
2
Order By: Relevance
“…Therefore, the expectant mothers are relatively young. A Malaysian study carried out in 2007 found 29.8 years ± 4.6 years and 29 years ± 4.4 years, respectively, which is higher than ours [4]. The fact that our study was conducted in a single hospital could account for this gap, since not all age ranges were necessarily enrolled.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Therefore, the expectant mothers are relatively young. A Malaysian study carried out in 2007 found 29.8 years ± 4.6 years and 29 years ± 4.4 years, respectively, which is higher than ours [4]. The fact that our study was conducted in a single hospital could account for this gap, since not all age ranges were necessarily enrolled.…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies reported this fact. In Iran, Atrian et al [3] concluded that when full term expectant mothers engaged in sexuality during low-risk pregnancies, it prevented progress towards cases of prolonged pregnancies, in Malaysia, Tan et al [4] studied the relationship between sexual activity and patients going into labor from 37 weeks of gestation to full term and she concluded a decrease in the development towards prolonged pregnancies in 72% of cases. The expectant mothers practicing sexual intercourse during pregnancy were less likely to experience prolonged pregnancies, spontaneous labor and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 small randomized trial that attempted to address this question, women were randomized to a group advised to have coitus versus a control group which was not. In this study, the women advised to have coitus did so more often (60% vs. 40%), but there was no measurable difference in the rate of spontaneous labor in this underpowered study (95). Similarly, the efficacy of acupuncture for induction of labor cannot be definitively assessed because of the paucity of trial data and requires further examination (96,97).…”
Section: Prevention Of Postterm Pregnancymentioning
confidence: 71%
“…One RCT is too small for meaningful guidance (97). In another RCT, compared with no such advice, advice for coitus was associated with more coital activity (60% vs. 40%), but similar rates of spontaneous labor (56% vs. 52%) (98).…”
Section: Sexual Intercoursementioning
confidence: 95%